Estimating roe deer and wild boar abundance and habitat use in a heterogeneous landscape of Northern Portugal - Oliveira, Marta Sofia Teixeira (2021)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia